Anabolic Androgenic Steroids Induce Reversible Left Ventricular Hypertrophy and Cardiac Dysfunction. Echocardiography Results of the HAARLEM Study - Smit, Diederik L.; Voogel, A. J.; Heijer, Martin den; Ronde, Willem de (Frontiers in Reproductive Health, 2021)
Background: The use of anabolic androgenic steroids (AAS) is not uncommon among strength athletes. Several cross-sectional studies have linked AAS use to heart disease, but a causal role for AAS is not certain and it is unknown whether cardiac changes are reversible. Methods: Men of at least 18 years old intending to start an AAS cycle on short notice were included for comprehensive 3D echocardiographic examination before (T0), at the end of the cycle (T1), and 1 year after inclusion (T2) after a recovery period. Details of the AAS cycle performed and the use of other performance and image-enhancing drugs (PIEDs) as well as illicit drug use were recorded. Trend analysis and multivariable regression analysis were performed with mixed effects linear models. Results: Thirty-one subjects were included. Between start (T0) and end of the cycle (T1), after a median AAS cycle duration of 16 weeks, 3D left ventricular ejection fraction declined with 4.9% (CI −7.2 to −2.5, P < 0.001), E/A-ratio declined with−0.45 (CI −0.69 to −0.21, P < 0.001), and 3D left atrial volume increased with 9.2 ml (CI 2.9–15.4, P = 0.004). Left ventricular mass increased with 28.3 g (CI 14.2–42.4, P < 0.001) and was positively correlated with AAS average weekly dose. After a median recovery time of 8 months (T2), all parameters returned to baseline. Conclusion: AAS induce left ventricular hypertrophy and impaired systolic and diastolic function in amateur strength athletes. The structural cardiac changes are positively associated with AAS dose and complete recovery occurred after AAS were discontinued.